2004
DOI: 10.1890/03-0251
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Lung-Regulated Buoyancy Control for Dive Depth and Duration

Abstract: Among air‐breathing divers, control of buoyancy through lung volume regulation may be most highly developed in marine turtles. In short, the turtle lung may serve a dual role as both an oxygen store and in buoyancy control. A simple model is developed to show that, for turtles diving up to the maximum depth at which they can still use their lungs to attain neutral buoyancy, the total oxygen store will increase greatly with dive depth, and hence a corresponding increase in dive duration is predicted. Time–depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 21 publications
4
72
0
1
Order By: Relevance
“…The duration of a turtle's dive is dependent on both the size of a breath taken at the surface and the energy expenditure during a dive. The size of the breath can also influence turtle dive depth as it impacts the depth of neutral buoyancy (Hays et al 2004); turtles modulate the size of their breath based on the intent of the dive (Okuyama et al 2014). Accordingly, we modeled the effect of dive depth and activity level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of a turtle's dive is dependent on both the size of a breath taken at the surface and the energy expenditure during a dive. The size of the breath can also influence turtle dive depth as it impacts the depth of neutral buoyancy (Hays et al 2004); turtles modulate the size of their breath based on the intent of the dive (Okuyama et al 2014). Accordingly, we modeled the effect of dive depth and activity level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The change in flipper angular velocity over the course of the dive can be attributed to changes in buoyancy that occur as a result of changing pressure with depth (Lovvorn et al 1991, 1999, Williams et al 2000, Hays et al 2004). Having inhaled a particular amount of air, and having a fixed amount of air in the plumage (Wilson et al 1992), a descending penguin must work against the upthrust in order to descend although, at constant speed, the power associated with this will decrease with increasing depth, as the air volume will be compressed, resulting in reduced upthrust.…”
Section: Discussionmentioning
confidence: 99%
“…An analogous situation has been reported for turtles, where those lying on the seabed can only do so motionless, and therefore with minimum energy expenditure, if they are negatively buoyant. This means that their lung volumes must be regulated, giving them less air at shallower depths (Hays et al 2004). However, turtles are essentially benthic and move comparatively slowly, therefore inspired air volume is not expected to vary greatly from dive to dive, whereas Magellanic penguins, with their pelagic diving behaviour (Peters et al 1998) may change the depth of the bottom phase substantially on a dive to dive basis and must correct accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Paulev showed that rapid, repetitive breath holding in human divers results in DCS (Paulev, 1965). The paradox of marine mammals, birds and reptiles diving routinely to substantial depths without apparent acute or chronic symptoms of DCS has aroused the curiosity of many scientists (Costa et al, 2004;Fossette et al, 2010;Hays et al, 2004;Kooyman, 2006;Ridgway and Howard, 1979;Scholander, 1940;Wilson et al, 1992). Anatomical adaptations thought to be important include: lung collapse, the atelectic collapse of alveoli to shunt blood away from gas exchange surfaces; tracheobronchial compliance changes (Bostrom et al, 2008); and blood redistribution into the rete mirabile in cetaceans and blood sinuses in pinnipeds.…”
Section: Introductionmentioning
confidence: 99%